Graphene quantum dot with covalently linked Rhodamine dye: a high efficiency photocatalyst for hydrogen evolution. (15th October 2020) - Dinda, Diptiman; Park, Hyunho; Lee, Hyun-Jun; Oh, Sangyoon; Park, Soo Young
Abstract: Designing metal free photocatalyst for solar water splitting is an emerging field of research. Although graphene quantum dot (GQD) has been explored as a potential photocatalyst, their performance remains inherently limited by poor visible light absorption and p-type conductivity. To address this problem, we have covalently functionalized GQD with visible light active photosensitizer Rhodamine 123. It was found that this dye-sensitized GQD could make quite stabilized photocatalytic hydrogen evolution reaction (HER) under visible light irradiation, which is in striking contrast to the virtually inactive photocatalytic HER performance of control GQD without dye. Efficient photo-induced electron transfer from Rhodamine 123 to GQD and also the transformation of p type GQD to the n-p ambipolar semiconductor, both boosted by covalent bonding, are responsible for such high photocatalytic HER performance. Observation of negative photocurrent at zero bias voltage during transient photocurrent measurement, also suggests its promising potential in the metal free photocathode system to achieve photoelectrochemical H2 production. Graphical abstract: Image 1 Rhodamine123 attached Graphene quantum dot (GQD) acts as a metal free photocatalyst for H2 production under visible light irradiation. Covalent linkage facilitates better electron transfer as well as superior e-h separation by passivating charge trap centers in GQD making it 'n-p' type ambipolar semiconductor for efficient H2 evolution reaction. Highlights: Rhodamine dye is covalently connected with GQD via amide linkage. It produces H2 efficiently under visible light irradiation without any co-catalyst. Covalent bonding quickly transfers photo-induced electrons from Rhodamine to GQD. Amide linkage passivates charge trap states in GQD making it 'n-p' semiconductor . Negative photocurrent at zero bias represents its photo cathode behavior.